Existence of the day-of-the-week effect in FTSE Bursa Malaysia - Hooi, Hooi Lean; Veronica Kah Min Tan, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This paper investigates the existence of day-of-the-week effect for ten FTSE Bursa Malaysia indices. Standard procedure of determining calendar anomaly with additional GARCH related models are employed to determine the significance of the day-of-the-week effect. Results suggest that the day-of-the-week effect only exist for the FTSE Bursa Malaysia MESDAQ Index. However, the effect might be due to changing volatility since the negative and lowest Monday return does not appear to be significant in the EGARCH model